Chiral CuO@Ni with continuous macroporous framework and its high catalytic activity for electrochemical water oxidation. (19th February 2021) - Zhang, Wenyan; Wang, Wei; Hu, Yingfei; Guan, Hangmin; Yang, Xiaoli; Hao, Lingyun
Abstract: Electrochemical water splitting is considered as a promising approach to storing renewable electricity in the form of hydrogen fuel. In this work, we report the design and electrocatalytic properties of chiral CuO@Ni with three dimensional (3D) continuous macroporous framework. With the chiral CuO@Ni as anode, the OER overpotential required to achieve the current density of 10 mA/cm 2 was as low as 110 mV in 0.1 M KOH electrolyte, and the hydrogen production rate of water splitting reaction could reach 1070 nL/s. Moreover, the OER overpotential could be regulated easily by controlling the deposition time of chiral CuO layer on Ni. The high catalytic activity of chiral CuO@Ni for water splitting is closely associated with the Chiral-induced spin selectivity ( CISS ) effect, the large reactive area provided by its 3D macroporous structure, and the effective cooperation between chiral CuO and Ni foam that facilitated the transportation of spin aligned electrons from chiral CuO layer to Ni. The results shown in this work indicate a simple and promising strategy to improve the electrocatalytic activity of other chiral earth-abundant catalysts for water splitting. Graphical abstract: This work shows the design and properties of chiral CuO@Ni with three dimensional continuous macroporous framework. The chiral CuO@Ni exhibited lower OER overpotential and larger current density than many CuO-based catalysts. Its high catalytic activity for water splitting reaction is attributed to the CISS effect of chiral CuO, the large reactive area of its 3D porous structure, and the synergistic interaction between the chiral CuO and the Ni foam. Image 1 Highlights: Chiral CuO@Ni with three dimensional continuous macroporous framework. Low OER overpotential (110 mV) to achieve 10 mA/cm 2 current density. Easy and effective way to enhance the activity of chiral earth-abundant catalyst.